Penerapan Uji Tahanan Tanah Dengan Metode Geolistrik Untuk Mendapatkan Peta Resistivitas Tanah Di Padang Panjang – Sumatera Barat - Amirul Latief Azzmi; Edy Ervianto; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Research on the application of the soil resistance test using the Geoelectric method was carried out on a public road near the white bridge of Silaing Bawah Village, Padang Panjang City, West Sumatra. Research with the Geoelectric method aims to obtain a soil resistivity map to provide information about soil and rock resistivity in the underground layers that can be analyzed in the field of Earth science. To find out the difference in resistivity of each soil layer, a 2D visual section in the form of color visuals is displayed using Res2Dinv software using the Dipole-dipole configuration. On the first track of ground resistivity map, the resistivity value A <4.655 Ωm - H> 635.5 Ωm and on the second track of ground resistivity map, the resistivity value of A <8.345 8.3m - H> 359 Ωm.Keywords: Dipole-dipole configuration, Geoelectric, Map of soil resistivity.